Biodiversity and technological properties of yeasts from Turkish sourdough - Arici, Muhammet; Ozulku, Gorkem; Yildirim, Rusen Metin; Sagdic, Osman; Durak, M. Zeki (KOREAN SOCIETY FOOD SCIENCE & TECHNOLOGY-KOSFOST, 2018)
In this study, yeasts were isolated and characterized from twelve traditional sourdough samples which belongs to Black Sea and Aegean regions of Turkey. Twenty six yeast species were isolated and identified by both 26S rDNA sequencing and FTIR spectroscopy. Saccharomyces cerevisiae (50%), Torulaspora delbrueckii (40%) and Kluyveromyces marxianus (10%) were found in 12 Turkish traditional sourdough samples. S. cerevisiae was found to be the most dominant species in Aegean region while T. delbrueckii was the most frequently isolated species in Black Sea region. Some technological properties of isolated yeast species such as acidity development, resistance to NaCI and potassium sorbate, and yeast effect on bread quality were investigated. Breads were prepared by S. cerevisiae TGM38 strain demonstrated the highest bread volume compared the other yeasts used in the study. This study showed the yeast diversity and technological properties of traditional Turkish sourdough breads fermented by chosen yeast species.
Keywords: Sourdough yeast; Technological properties; Sourdough bread; FTIR; 26S rDNA; IDENTIFICATION; BREAD; FERMENTATION; BACTERIA; CULTURES; DOUGH; Food Science & Technology